Assessment of functional relevance of genes associated with local temperature variables in Arabidopsis thaliana. (24th August 2022) - Jiang, Yuan; Wang, Zhixue; Du, Hui; Dong, Runlong; Yuan, Yaping; Hua, Jian
Abstract: How likely genetic variations associated with environment identified in silico from genome wide association study are functionally relevant to environmental adaptation has been largely unexplored experimentally. Here we analyzed top 29 genes containing polymorphisms associated with local temperature variation (minimum, mean, maximum) among 1129 natural accessions of Arabidopsis thaliana . Their loss‐of‐function mutants were assessed for growth and stress tolerance at five temperatures. Twenty genes were found to affect growth or tolerance at one or more of these temperatures. Significantly, genes associated with maximum temperature more likely have a detect a function at higher temperature, while genes associated with minimum temperature more likely have a function at lower temperature. In addition, gene variants are distributed more frequently at geographic locations where they apparently offer an enhanced growth or tolerance for five genes tested. Furthermore, variations in a large proportion of the in silico identified genes associated with minimum or mean‐temperatures exhibited a significant association with growth phenotypes experimentally assessed at low temperature for a small set of natural accessions. This study shows a functional relevance of gene variants associated with environmental variables and supports the feasibility of the use of local temperature factors in investigating the genetic basis of temperature adaptation. SUMMARY STATEMENT: Whether or not genetic variations associated with local environmental variables are functionally relevant to environmental adaptation have not been experimentally investigated. Here we analyzed top genes with polymorphisms associated with three temperature variables of 1129 natural accessions of Arabidopsis thaliana and showed a functional relevance of these genes in temperature responses, supporting the feasibility of using in silico environment association to investigate environmental adaptation.